Experimental investigations on the utilization of waste cooking oil based biodiesel & n-butanol in CI Engine - Manu, Jindal (My University, 2014)
In recent years, two problems roused people’s concern. One is energy crisis caused by the depleting of petroleum fuel. The other one is environmental issues such as greenhouse effect, global warming, etc. Therefore, renewable energy sources utilization technology and bio-energy production technology developed fast for solving such two problems. Biodiesel is receiving increased attention as an alternative, non-toxic, biodegradable, and renewable diesel fuel. The production of biodiesel from waste vegetable oil offers a triple-facet solution: economic, environmental and waste management. Butanol is a potential alternative to ethanol and offers many benefits including a much higher heating value and lower latent heat of vaporization. It also has a higher cetane number than ethanol and improved miscibility in diesel fuel. Additionally, butanol is less corrosive and less prone to water absorption than ethanol, which allows it to be transported using the existing fuel supply pipelines. Experimental work was conducted to evaluate the effect of using n-butanol-biodiesel-diesel blends on the engine performance parameter of a single cylinder direct injection compression ignition engine with the engine working at different loads. Blends of biodiesel-diesel fuel (B20, B40 and B60) and biodiesel-diesel-n butanol (nB10 and nB20) were prepared and engine performance parameters and emissions were checked. The performance parameters evaluated include brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), brake specific energy consumption (BSEC), brake power (BHP). Emission parameters included HC, CO2, CO, NOx, and smoke. Results were compared with the neat diesel. Emissions were reduced by 25-50% and efficiency increased by 13% with B20 blend. The experiment shows that 20% biodiesel blended with diesel and 10% n butanol blend gave best results and can be used without any modification in the diesel engine with point of view of decreased bsfc, increased efficiency and reduction in emissions.
M.Tech (EST) Dissertation
Keywords: Waste cooking oil; n-butanol; biodiesel; CI Engine